A genre analysis of research article ‘findings and discussion’ sections written by Indonesian undergraduate EFL students - Suherdi, Didi; Kurniawan, Eri; Lubis, Arif Husein (Indonesian Journal of Applied Linguistics, 2020)
The quality of findings and discussion (F D) section in a research article is crucial to elucidate the results of a particular inquiry and to situate the significance of the results in the body of knowledge through publications in scientific journals. Previous academic genre analysis has generated several models to help novice writers develop the rhetorical moves of the F D sections across disciplines. However, the study on the quality of the rhetorical moves in the undergraduate EFL students’ research articles is still scarce. Hence, this study seeks to examine the manifestation of rhetorical moves in the findings and discussion sections written by Indonesian undergraduate EFL students. A total of 113 unpublished ELT research articles from a state educational university in Bandung was selected as the target corpus. AntMover 1.10 was employed as the analysis tool. The top-down approach was carried out to obtain the existing rhetorical structure using Ruiying and Allison’s (2003) framework as the guideline. The bottom-up approach was used to scrutinize the linguistic realizations of the rhetorical moves. The findings demonstrated that, in the move level, most of the students’ F D sections had manifested the four moves, i.e., providing background information, reporting results, summarizing results, and commenting on results. However, in the step level, a number of F D sections did not provide detailed information regarding the sequence of the findings presentation, the analysis procedure to obtain the findings, the explanation for the findings, and the highlight of the significance of the findings. The randomized rhetorical patterns were also dominant. It can downgrade the clarity and rigor of the F D sections. Despite that, the linguistic realizations of the moves, particularly the tense and sentence voice, mostly conformed to the norms. The findings may serve as a reference to develop the teaching materials of English for research publication purposes (ERPP).